Corrections to “Sandpiper Optimization Algorithm With Region Growing Based Robust Retinal Blood Vessel Segmentation Approach” - Ibrahim Almohimeed; Mohamed Yacin Sikkandar; A. Mohanarathinam; Velmurugan Subbiah Parvathy; Mohamad Khairi Ishak; Faten Khalid Karim; Samih M. Mostafa (IEEE Access)
Presents corrections to the paper, (Corrections to “Sandpiper Optimization Algorithm With Region Growing Based Robust Retinal Blood Vessel Segmentation Approach”).